Assessment of listing and categorisation of animal diseases within the framework of the Animal Health Law (Regulation (EU) No 2016/429): Aujeszky's disease. (18th July 2017) - ,; More, Simon; Bøtner, Anette; Butterworth, Andrew; Calistri, Paolo; Depner, Klaus; Edwards, Sandra; Garin‐Bastuji, Bruno; Good, Margaret; Gortázar Schmidt, Christian; Michel, Virginie; Miranda, Miguel Angel; et al.
Abstract: Aujeszky's disease has been assessed according to the criteria of the Animal Health Law (AHL), in particular criteria of Article 7 on disease profile and impacts, Article 5 on the eligibility of Aujeszky's disease to be listed, Article 9 for the categorisation of Aujeszky's disease according to disease prevention and control rules as in Annex IV and Article 8 on the list of animal species related to Aujeszky's disease. The assessment has been performed following a methodology composed of information collection and compilation, expert judgement on each criterion at individual and, if no consensus was reached before, also at collective level. The output is composed of the categorical answer, and for the questions where no consensus was reached, the different supporting views are reported. Details on the methodology used for this assessment are explained in a separate opinion. According to the assessment performed, Aujeszky's disease can be considered eligible to be listed for Union intervention as laid down in Article 5(3) of the AHL. The disease would comply with the criteria as in sections 4 and 5 of Annex IV of the AHL, for the application of the disease prevention and control rules referred to in points (d) and (e) of Article 9(1). The animal species to be listed for Aujeszky's disease according to Article 8(3) criteria are mainly the species of the family of Suidae as susceptible species, although almost all mammals can be infected, and Sus scrofa as reservoir species.